Study of the physical and mechanical properties of a naturally reinforced composite after several recycling processes - SAHI, Samira (Biopolymer Applications Journal, 2025)
Composites based of Poly (vinyl Chloride) (PVC) reinforced with maize flour (MF) at proportion of 30 (%.Wt) were prepared. The objective of this work is to study the effect of the number cycle of the recycling in the physical, chemical and mechanical properties in this composite. Different characterization techniques were used to study the effect of the number of recycling cycles on the mechanical, physical and chemical properties of the materials developed. The results recorded after three cycles of recycling show an increase in tensile strength, in Young’s modulus and in water absorption of composites. However, a decrease in hardness is recorded. FTIR analysis showed no change in the absorption bands after recycling.